Do farming conditions influence brominated flame retardant levels in pig and poultry products? - A. Huneau-Salaün; R. Cariou; E. Royer; C. Jondreville; L. Balaine; C. Souchet; J. Coton; A. Vénisseau; R. Thomas; Y. Rousselière; A. Charpiot; P. Marchand; et al. (Animal, 2020)
Brominated flame retardants (BFR) are primarily used as flame retardant additives in insulating materials. These lipophilic compounds can bioaccumulate in animal tissues, leading to human exposure via food ingestion. Although their concentration in food is not yet regulated, several of these products are recognised as persistent organic pollutants; they are thought to act as endocrine disruptors. The present study aimed to characterise the occurrence of two families of BFRs (hexabromocyclododecane (HBCDD) and polybrominated diphenyl ethers (PBDE)) in hen eggs and broiler or pig meat in relation to their rearing environments. Epidemiological studies were carried out on 60 hen egg farms (34 without an open-air range, 26 free-range), 57 broiler farms (27 without an open-air range, 30 free-range) and 42 pig farms without an open-air range in France from 2013 to 2015. For each farm, composite samples from either 12 eggs, five broiler pectoral muscles or three pig tenderloins were obtained. Eight PBDE congeners and three HBCDD stereoisomers were quantified in product fat using gas chromatography–high-resolution mass spectrometry, or high-performance liquid chromatography–tandem mass spectrometry, respectively. The frequencies of PBDE detection were 28% for eggs (median concentration 0.278 ng/g fat), 72% for broiler muscle (0.392 ng/g fat) and 49% for pig muscle (0.403 ng/g fat). At least one HBCDD stereoisomer was detected in 17% of eggs (0.526 ng/g fat), 46% of broiler muscle (0.799 ng/g fat) and 36% of pig muscle (0.616 ng/g fat). Results were similar in concentration to those obtained in French surveillance surveys from 2012 to 2016. Nevertheless, the contamination of free-range eggs and broilers was found to be more frequent than that of conventional ones, suggesting that access to an open-air range could be an additional source of exposure to BFRs for animals. However, the concentration of BFRs in all products remained generally very low. No direct relationship could be established between the occurrence of BFRs in eggs and meat and the characteristics of farm buildings (age, building materials). The potential presence of BFRs in insulating materials is not likely to constitute a significant source of animal exposure as long as the animals do not have direct access to these materials.